Airhead - Cabot, Meg (New York Point, 2008)
Sixteen-year-old Emerson Watts, an advanced placement student with a disdain for fashion, is the recipient of a "whole body transplant" and finds herself transformed into one of the world's most famous teen supermodels
Hurg
5 8
Keywords: Identity -- Fiction; Models -- Fiction; Transplantation of organs, tissues -- Fiction